Semantic Web and Peer-to-Peer Decentralized Management and Exchange of Knowledge and Information - Staab, Steffen; Stuckenschmidt, Heiner; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
Just like the industrial society of the last century depended on natural resources, today’s society depends on information and its exchange. Staab and Stuckenschmidt structured the selected contributions into four parts: Part I, "Data Storage and Access", prepares the semantic foundation, i.e. data modelling and querying in a flexible and yet scalable manner. These foundations allow for dealing with the organization of information at the individual peers. Part II, "Querying the Network", considers the routing of queries, as well as continuous queries and personalized queries under the conditions of the permanently changing topological structure of a peer-to-peer network. Part III, "Semantic Integration", deals with the mapping of heterogeneous data representations. Finally Part IV, "Methodology and Systems", reports experiences from case studies and sample applications. The overall result is a state-of-the-art description of the potential of Semantic Web and peer-to-peer technologies for information sharing and knowledge management when applied jointly.
Peer-to-Peer and Semantic Web -- Peer-to-Peer and Semantic Web -- Data Storage and Access -- An RDF Query and Transformation Language -- RDF and Traditional Query Architectures -- Query Processing in RDF/S-Based P2P Database Systems -- Querying the Network -- Cayley DHTs — A Group-Theoretic Framework for Analyzing DHTs Based on Cayley Graphs -- Semantic Query Routing in Unstructured Networks Using Social Metaphors -- Expertise-Based Peer Selection -- Personalized Information Access in a Bibliographic Peer-to-Peer System -- Designing Semantic Publish/Subscribe Networks Using Super-Peers -- Semantic Integration -- Semantic Coordination of Heterogeneous Classifications Schemas -- Semantic Mapping by Approximation -- Satisficing Ontology Mapping -- Scalable, Peer-Based Mediation Across XML Schemas and Ontologies -- Semantic Gossiping: Fostering Semantic Interoperability in Peer Data Management Systems -- Methodology and Systems -- A Methodology for Distributed Knowledge Management Using Ontologies and Peer-to-Peer -- Distributed Engineering of Ontologies (DILIGENT) -- A Peer-to-Peer Solution for Distributed Knowledge Management -- Xarop, a Semantic Peer-to-Peer System for a Virtual Organization -- Bibster — A Semantics-Based Bibliographic Peer-to-Peer System.
Keywords: Information storage and retrieval; Computer communication systems; Application software; Artificial intelligence; Information Storage and Retrieval; Computer Communication Networks; Information Systems Applications (incl. Internet).; Artificial Intelligence